1998
DOI: 10.1074/jbc.273.46.30736
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant IκB Kinases α and β Are Direct Kinases of IκBα

Abstract: Activation of the transcription factor NF-B is regulated by the phosphorylation and subsequent degradation of its inhibitory subunit, IB. A large multiprotein complex, the IB kinase (IKK), catalyzes the phosphorylation of IB. The two kinase components of the IKK complex, IKK␣ and IKK␤, were overexpressed in insect cells and purified to homogeneity. Both purified IKK␣ and IKK␤ specifically catalyzed the phosphorylation of the regulatory serine residues of IB␣. Hence, IKK␣ and IKK␤ were functional catalytic subu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
84
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 20 publications
10
84
2
Order By: Relevance
“…In the case of Ser 342 , it is unclear why this residue is important for p50 DNA binding. Phosphorylation may not be involved, as substitution with threonine failed to retain p50 DNA binding, although it is known that some kinases, notably IKKs, strongly prefer serine over threonine (46). In addition, despite their proximity, Ser 342 is not involved in phosphorylation of Ser 337 , as phosphorylation of Ser 337 by PKA was not disrupted by mutation of Ser 342 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the case of Ser 342 , it is unclear why this residue is important for p50 DNA binding. Phosphorylation may not be involved, as substitution with threonine failed to retain p50 DNA binding, although it is known that some kinases, notably IKKs, strongly prefer serine over threonine (46). In addition, despite their proximity, Ser 342 is not involved in phosphorylation of Ser 337 , as phosphorylation of Ser 337 by PKA was not disrupted by mutation of Ser 342 .…”
Section: Discussionmentioning
confidence: 98%
“…Although we have shown that Ser 337 is a target for phosphorylation by PKA in vitro, making it highly probable that p50 is regulated by PKA, it should be noted that the sequence surrounding Ser 337 also fits the profile of several other kinases such as CaMII, casein kinase II, and protein kinase G. Nonetheless, the conformational change induced by the phosphorylation of p50 Ser 337 could be different from that induced by phosphorylation of p65 Ser 276 because p50 lacks a transactivation domain. The crystal structures of DNA-bound NF-B show that Ser 337 is proximal to the hinge region linking the N-terminal and C-terminal domains of p50 (46). Serine 337 resides on the outer surface of p50, making it easily accessible by kinases.…”
Section: Discussionmentioning
confidence: 99%
“…IKK complex is composed of two catalytic subunits, IKKα (or IKK1) and IKKβ (IKK2), and a regulatory subunit, IKKγ/NEMO/IKKAP1 (reviewed in May and Ghosh, 1998;Zandi and Karin, 1999). IKKα and IKKβ are Ser/Thr kinases of similar structure which can form homodimers and heterodimers in vitro, and purified recombinant form of each can directly phosphorylate IκBα and β at proper sites (Lee et al, 1998;Li et al, 1998;Zandi et al, 1998). The activity of IKKα and IKKβ was shown to depend on their phosphorylation at specific serine residues (Ser-176/180 of IKKα and Ser-177/181 of IKKβ) located in the T (activation) loop of the kinase domain, and substitution of these sites with glutamate, which mimic the effect of phosphoserine, generated constitutively activated form of IKKα and IKKβ (Mercurio et al, 1997;Ling et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Two catalytic subunits (termed IKK-1 and IKK-2) of IKK have recently been identified, cloned, and shown to be widely expressed in human tissues (12)(13)(14)(15)(16)(17). The use of gene-targeting experiments have clearly shown that all known proinflammatory stimuli, including cytokines, viruses, and lipopolysaccharide (LPS) require the IKK-2 subunit for NF-B activation (for a review see Ref.…”
mentioning
confidence: 99%